The Implementation of Problem-Based Learning Model to Improve Student Learning Outcomes - Sumual, Shelty D M; Lumapow, Harol R; Tuerah, Philotheus E A; Theno, Ignatius R; Dondokambey, Robby; Liow, Evans S (International Journal of Information Technology and Education, 2024)
Objective study This for know Application Model Learning Problem Based For Increase Results Study Computer And Network Base class X TKJ State Vocational School 1 Bitung. The research method used is classroom action research (PTK). The research took place in 2 cycles consisting of 8 meetings. Every cycle consists of planning action, implementation action, observation, and reflection. The subjects in the research were students of class X TKJ SMK Negeri 1 Bitung consisting of 32 person students. The data intake in a study covers data on student learning outcomes from the knowledge (cognitive) domain and the psychomotor (skills) domain. The research results show that the application of the problem-based learning model can improve computer and basic network learning outcomes for classroom students X TKJ vocational school Country 1 Bitung. This can prove that there is an enhancement in student learning outcomes in each cycle. In cycle I the percentage of completeness of students' knowledge of learning outcomes was 72%, while in cycle II the percentage of completeness of learning outcomes knowledge students increased become 94%. Then For cycle I the percentage of completeness of students' skills learning outcomes was 75%, while in cycle II the percentage of completeness of students' skills learning outcomes increased to 100%. Based on the results obtained, it can be concluded that the application of the problem-based learning model can improve computer and basic network learning outcomes for class X TKJ SMK Negeri 1 Bitung students.